2020
DOI: 10.3390/molecules25225385
|View full text |Cite
|
Sign up to set email alerts
|

Possible Participation of Ionotropic Glutamate Receptors and l-Arginine-Nitric Oxide-Cyclic Guanosine Monophosphate-ATP-Sensitive K+ Channel Pathway in the Antinociceptive Activity of Cardamonin in Acute Pain Animal Models

Abstract: The perception of pain caused by inflammation serves as a warning sign to avoid further injury. The generation and transmission of pain impulses involves various pathways and receptors. Cardamonin isolated from Boesenbergia rotunda (L.) Mansf. has been reported to exert antinociceptive effects in thermal and mechanical pain models; however, the precise mechanism has yet to be examined. The present study investigated the possible mechanisms involved in the antinociceptive activity of cardamonin on protein kinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…To this end, we initially assessed the modulation of the glutamatergic and nitrergic pathways, along with the evaluation of cGMP modulation. These pathways, particularly the NMDA receptor, NOx modulation (nitrergic pathway), and cGMP pathway, collectively constitute a pivotal mechanism for combating nociception (NMDA/NO/cGMP pathway) [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…To this end, we initially assessed the modulation of the glutamatergic and nitrergic pathways, along with the evaluation of cGMP modulation. These pathways, particularly the NMDA receptor, NOx modulation (nitrergic pathway), and cGMP pathway, collectively constitute a pivotal mechanism for combating nociception (NMDA/NO/cGMP pathway) [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the fruit and rhizomes of Alpinia species, cardamonin is also isolated from various plants of the Zingiberaceae family [ 4 ]. Cardamonin is known to possess diverse pharmacological properties against numerous pathological conditions including inflammation [ 45 ] and cancer [ 46 ]. The multitargeting properties of cardamonin is the key to its therapeutic effects against chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…VGKCs play an essential role in the potential membrane regulation of primary OA chondrocytes and mediate electromechanical transduction [ 72 ]. Specifically, VGKCs subtypes (Kv7) [ 73 ], large-conductance calcium-activated K + channel (BKCa), Kir2.1, ATP-sensitive potassium channel (K-ATP), and twik-related spinal cord K + (TRESK) are closely associated with OA pain [ [74] , [75] , [76] ]. It has been reported that specific activation of the neuronal Kv7 channel in the OA rat; when the Kv7 channel is inhibited, mechanical ectopic pain and heat hyperalgesia can be alleviated, thus relieving pain caused by OA [ 77 ].…”
Section: Literature Selection Methodsmentioning
confidence: 99%